The impact of social ties on homelessness - Kevin C. Corinth; Claire Rossi-de Vries (American Enterprise Institute (AEI), 2017)
While almost all homeless people are poor, most poor people do not experience homelessness. We use a detailed national survey to explore the role of social ties - including connection to relatives, friends and religious community - in explaining why only a subset of poor adults fall into homelessness.
Keywords: A; 330; Poverty; homelessness